Effect of Benson Relaxation Technique Requirement Compliance Against Sleep In Elderly In Semarang City Regional Health Center Srondol - Purnomo Purnomo; Ramelan Sugijana; Muhamad Syamsul Arif Setiyo Negoro (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2013)
Elderly in 2025 will reach 1.2 billion, of which 1 billion are in developing countries, including Indonesia (Nugroho, 2000). Life expectancy in Indonesia (UHH) is expected to increase from 66.2 years in 2004 to 70.6 years in 2009. And in 2010 estimated the population of elderly (seniors) in Indonesia, amounting to 24 million people or 9.77% of the total population. Objectives determine the effect of Benson relaxation techniques to meet the needs of sleep in the elderly in the city of Semarang Srondol Health Center. Quasy research used experimental research with pretest - posttes with control group design. Elderly population in this study are listed in IHC Health Center Srondol elderly in the city of Semarang. Sample required is 30 (thirty) people. Univariate and Bivariate analysis of quantitative data collection was performed on 30 elderly respondents with sleep disturbances, while giving them questions to respondents in the form of 41 questions with answers that are already available .Discussion of the results of research based on the results of Wilcoxon Signed Ranks Test of the overall sample (30 respondents aged) scores are rising, while pre-test needs sleep categories are as many as 19 people (63.3%), while post-test after the treatment of 19 elderly people to be good ( 63.3%), at the time of pre-test category ugly 11 elderly people (36.7%), the treatment time to 11 people were elderly (36.7%) no significant difference before treatment with the need to sleep after perlakuann which is based on test results wilkokson at the significance level get 0:00. That no effect of Benson relaxation training with a religious approach to the reduction of insomnia disorders. Conclusions based on this study concluded that the reduction in the higher rate of insomnia in the experimental group compared with the control group, then after a given experimental treatment group experienced decreased levels of insomnia. Posyandu suggestions elderly in Puskesmas Srondol expected berpartitisipatif in the management of insomnia by teaching relaxation techniques benson. Society (the elderly) are given enough information about insomnia (sleep disorders), and combating insomnia with therapies benson